Surgical Recovery - Sozen, Selim (IntechOpen, 2020)
Recovering from surgery is greatly dependent upon the type of surgery you will be having. Enhanced recovery pathways include preoperative, intraoperative, and postoperative practices that decrease complications and accelerate recovery. How long it takes you to fully recover from your surgery will depend on many things, including: • your age • your health before the surgery • the extent of your injuries • the success of your rehabilitation • the amount of rest you get. It may take a few days or a week to recover from a less complex operation, but it can take a few months to recover from major surgery. The American Society of Anesthesiologists Physical Status (ASA-PS) classification has long been used as a ranking system that quantifies patient health before anesthesia and surgery. It is widely used to determine a patient's likelihood of developing postoperative complications. ERAS is the acronym of Enhanced Recovery After Surgery: a multimodal perioperative approach based on the best medical evidence. The aim of this program is to try to change the physiological and psychological responses to major surgery. Malnutrition is one of the most important patient-related factors affecting morbidity and mortality in surgical patients. In addition, infections are important in the recovery process after surgery.